2011
DOI: 10.1016/j.seizure.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Infantile spams without hypsarrhythmia: A study of 16 cases

Abstract: The patients in this series may be considered to have a variant of West syndrome rather than an electroclinically distinct epileptic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 15 publications
(64 reference statements)
0
47
0
Order By: Relevance
“…Taurine was prescribed in order to prevent VGB-induced retinal phototoxicity (Jammoul et al, 2009). ESWH associated with TS may be a variant of focal spasms (Caraballo et al, 2003) and, as suggested by Caraballo et al (2011), might be considered an epileptic syndrome referred to as "ESWH in infancy and childhood. "…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taurine was prescribed in order to prevent VGB-induced retinal phototoxicity (Jammoul et al, 2009). ESWH associated with TS may be a variant of focal spasms (Caraballo et al, 2003) and, as suggested by Caraballo et al (2011), might be considered an epileptic syndrome referred to as "ESWH in infancy and childhood. "…”
Section: Discussionmentioning
confidence: 99%
“…Hypsarrhythmia is not found in all cases and ES without hypsarrhythmia (ESWH) have been described in some series of patients, occurring either in infancy or childhood, and are associated with different conditions (Goldstein and Slomski, ; Caraballo et al , ).…”
mentioning
confidence: 99%
“…Thereafter, only those infants with hypsarrhythmia on the EEG were included in the study because this is mandatory for the classification of infantile spasms. Infants with spasms but no hypsarrhythmia demonstrate different developmental progression patterns and were likely to bias the developmental attainment results . Children younger than 2 months or older than 3 years 6 months, with a diagnosis of tuberous sclerosis or any contraindications for the use of hormonal therapies, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the international West Delphi Group consensus statement did not regard the presence of hypsarrhythmia as essential for the diagnosis of ISS [1], and correctly refocused the core of the electroclinical disorder on the ictal event associated with an electrodecrement on EEG in an appropriately aged child. ISS without hysparrhythmia are well documented [9]. We will continue to refer to the disorder as infantile spasms , while recognizing that in some children they may not occur during infancy, and may not manifest as classic flexor or extensor spasms, and hypsarrhythmia may only be an associated feature of the interictal EEG.…”
Section: Introductionmentioning
confidence: 99%